Guidelines for the management of AIDS education in the curriculum in schools and institutions in CAREC member countries (CAREC Port of SpainTT, 1988)
Provides information that would assist education personnel in developing an AIDS education curriculum which could be adapted and modified to suit each education system in CAREC member countries.
DC